Collagenase treatment of Dupuytren's contracture using a modified injection method: A prospective cohort study of skin tears in 164 hands, including short-term outcome. (4th May 2015) - Atroshi, Isam; Nordenskjöld, Jesper; Lauritzson, Anna; Ahlgren, Eva; Waldau, Johanna; Waldén, Markus
Abstract : Background and purpose — Treatment of Dupuytren's contracture (DC) with collagenase Clostridium histolyticum (CCH) consists of injection followed by finger manipulation. We used a modified method, injecting a higher dose than recommended on the label into several parts of the cord, which allows treatment of multiple joint contractures in 1 session and may increase efficacy. We studied the occurrence of skin tears and short-term outcome with this procedure. Patients and methods — We studied 164 consecutive hands with DC, palpable cord, and extension deficit of ≥ 20º in the metacarpophalangeal (MCP) and/or proximal interphalangeal (PIP) joint (mean patient age 70 years, 82% men). A hand surgeon injected all the content of 1 CCH vial (approximately 0.80 mg) into multiple spots in the cord and performed finger extension under local anesthesia after 1 or 2 days. A nurse recorded skin tears on a diagram and conducted a standard telephone follow-up within 4 weeks. A hand therapist measured joint contracture before injection and at a median of 23 (IQR: 7–34) days after finger extension. Results — A skin tear occurred in 66 hands (40%). The largest diameter of the tear was ≤ 5 mm in 30 hands and > 10 mm in 14 hands. Hands with skin tear had greater mean pretreatment MCP extension deficit than those without tear: 59º (SD 26) as opposed to 32º (SD 23). Skin tear occurred in 21 of 24 hands with MCP contracture of ≥ 75º. All tears healed with open-wound treatment. No infections occurred. Mean improvement in total (MCP + PIP) extension deficit was 55º (SD 28). Interpretation — Skin tears occurred in 40% of hands treated with collagenase injections, but only a fifth of them were larger than 1 cm. Tears were more likely in hands with severe MCP joint contracture. All tears healed without complications. Short-term contracture reduction was good.